2022
DOI: 10.1017/ash.2022.310
|View full text |Cite
|
Sign up to set email alerts
|

The role of the clinical pharmacist in antimicrobial stewardship in Asia: A review

Abstract: Clinical pharmacist-driven antimicrobial stewardship programs (ASPs) have been successfully implemented. Although relevant guidance and several studies suggest that clinical pharmacists be integrated into the current ASP team model, barriers still exist in Asia, primarily due to lack of dedicated personnel and lack of career advancement. We review the effectiveness and the ideal role of clinical pharmacist among ASPs in Asia. Several studies conducted in Asia have shown the effectiveness of pharmacist-led ASP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…They play an important role in the development of antibiotics treatment plans according to the PK/PD theory of antimicrobial drugs [18].Other factors needed to be considered include the severity of the patient's condition, site of infection, tissue penetration, antimicrobial drug selection, clinical e cacy, safety, possible pathogenic bacteria, assessment of antimicrobial resistance, protein binding rate, and liver and kidney function. Clinical pharmacist intervention can reduce the rate of unreasonable drug application [19,20,21], shorten the length of hospital stay of patients, lower the incidence of adverse drug reactions, and improve the effect of anti-infection treatment. Daijing Dong et al [22] found the rational rate of prophylactic use of antibiotics in class I incisions was signi cantly improved, and the course of medication was obviously reduced before and after the intervention of clinical pharmacists.Meanwhile, other studies also pointed out [23,24] that the participation of clinical pharmacists in the consultation and individualized adjustment of medication regimens can ensure that patients receive more economic and effective treatment, and have a positive impact on reducing the inhospital mortality of patients with multi-drug resistant infection.…”
Section: Effect Of Re Ned Management Of Antibiotics Led By Clinical P...mentioning
confidence: 99%
“…They play an important role in the development of antibiotics treatment plans according to the PK/PD theory of antimicrobial drugs [18].Other factors needed to be considered include the severity of the patient's condition, site of infection, tissue penetration, antimicrobial drug selection, clinical e cacy, safety, possible pathogenic bacteria, assessment of antimicrobial resistance, protein binding rate, and liver and kidney function. Clinical pharmacist intervention can reduce the rate of unreasonable drug application [19,20,21], shorten the length of hospital stay of patients, lower the incidence of adverse drug reactions, and improve the effect of anti-infection treatment. Daijing Dong et al [22] found the rational rate of prophylactic use of antibiotics in class I incisions was signi cantly improved, and the course of medication was obviously reduced before and after the intervention of clinical pharmacists.Meanwhile, other studies also pointed out [23,24] that the participation of clinical pharmacists in the consultation and individualized adjustment of medication regimens can ensure that patients receive more economic and effective treatment, and have a positive impact on reducing the inhospital mortality of patients with multi-drug resistant infection.…”
Section: Effect Of Re Ned Management Of Antibiotics Led By Clinical P...mentioning
confidence: 99%
“…Additionally, the infectious disease physician collaborates with other healthcare professionals to provide education and training on infection control practices. By staying updated on the latest research and guidelines, they can effectively contribute to the prevention and management of infectious diseases in healthcare settings [ 10 ].…”
Section: Reviewmentioning
confidence: 99%
“…Pharmacists are well positioned to act as essential members of hospital ASPs, ensuring that regulatory requirements of ASPs are fulfilled due to their everyday multi-disciplinary collaborations [ 11 ]. Pharmacists have an important role in ASPs, transcending the patient care continuum and the healthcare system [ 5 , 6 ]. This role includes the following: optimizing prescribing behavior in inpatient, ambulatory, and emergency care units, monitoring and evaluating antibiotic use, and the development and review of policies and protocols for antibiotics, infection prevention and control, and integrated rapid diagnostic testing [ 5 , 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists have an important role in ASPs, transcending the patient care continuum and the healthcare system [ 5 , 6 ]. This role includes the following: optimizing prescribing behavior in inpatient, ambulatory, and emergency care units, monitoring and evaluating antibiotic use, and the development and review of policies and protocols for antibiotics, infection prevention and control, and integrated rapid diagnostic testing [ 5 , 6 , 11 , 12 ]. Moreover, pharmacists also conduct ASP education, training, public engagement, and antibiotic stewardship leadership and coordination in their working environment [ 5 , 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%